Anti-Inflammatory and Antioxidant Activities of the Methanolic Extract of Cyrtocarpa procera Bark Reduces the Severity of Ulcerative Colitis in a Chemically Induced Colitis Model - Mario Rodriguez-Canales; Elizdath Martinez-Galero; Alma D. Nava-Torres; Luvia E. Sanchez-Torres; Leticia Garduño-Siciliano; Maria Margarita Canales-Martinez; Luis I. Terrazas; Marco A. Rodriguez-Monroy (Hindawi Limited, 2020)
Cyrtocarpa procera is a plant used in traditional Mexican medicine to treat different gastrointestinal problems. Here, we investigated the effects of a C. procera methanolic extract in DSS-induced colitis mice. Ulcerative colitis (UC) was induced by administering 4% DSS in drinking water to female BALB/c mice. Compared to untreated mice with UC, the treatment group receiving the C. procera extract presented less severe UC symptoms of diarrhea, bleeding, and weight loss. Additionally, colon shortening was significantly reduced, and at the microscopic level, only minor damage was observed. Levels of proinflammatory cytokines such as TNF-α, IL-1β, and IFNγ in serum as well as the MPO activity in the colon were significantly reduced in the C. procera methanolic extract-treated group. Moreover, the extract of C. procera reduced oxidative stress during UC, preventing the deterioration of the activity of antioxidant enzymes such as SOD, CAT, and GPx. Additionally, the extract decreased lipid peroxidation damage and its final products, such as malondialdehyde (MDA). In agreement with this, in vitro assays with the C. procera extract displayed good antioxidant capacity, probably due to the presence of polyphenolic compounds, in particular the flavonoids that were identified, such as chrysin, naringenin, kaempferol, and catechin, which have been reported to have anti-inflammatory and antioxidant activities. Therefore, the improvement of UC by the C. procera methanolic extract may be related to the action mechanisms of these compounds.